The scope of Section 181 as a minority protection provision / Andrew Winston Kaya - Winston Kaya, Andrew (1986)
This paper is an endeavor to determine the scope of protection as provided for by section 181 of the Malaysian Companies Act of 1965 by referring to cases that have interpreted the section.